PALLADIUS OF HELENOPOLIS: A PARTY AND ITS SUPPORTERS IN THE CHURCH OF THE LATE FOURTH CENTURY1 - Hunt, E. D. (1973)
E. D. HUNT; PALLADIUS OF HELENOPOLIS: A PARTY AND ITS SUPPORTERS IN THE CHURCH OF THE LATE FOURTH CENTURY1, The Journal of Theological Studies, Volume XXIV, Iss